THE EFFECTIVENESS OF DEBATES IN ENGLISH SPEAKING DEVELOPMENT - Maxmanazarova Feruza Ismoilovna; Tohirova Laylo Alimardon qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores the pedagogical effectiveness of classroom debates as a primary instrument for enhancing English speaking proficiency among EFL (English as a Foreign Language) learners. In the contemporary educational landscape, transitioning from passive language comprehension to active communicative competence remains a critical challenge; thus, this research investigates how structured argumentation bridges this gap. Utilizing a quantitative survey methodology among a specific cohort of learners, the study examines the correlation between competitive debating and the development of oral fluency, critical thinking, and communicative confidence. The research provides a comprehensive analysis of learner perceptions, highlighting significant improvements in argumentative logic and speech spontaneity. Furthermore, the paper identifies prevalent psychological and lexical barriers, such as learner anxiety and vocabulary limitations, offering actionable insights for their mitigation. By synthesizing empirical data with existing linguistic theories, the article establishes a robust framework for integrating debate-centered instruction into the curriculum. Ultimately, this research serves as a strategic guide for educators and curriculum designers aiming to foster a more dynamic, student-centered, and cognitively engaging environment for language acquisition in non-native contexts.